2015
DOI: 10.3390/molecules200711861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antiviral Bioactivity of Novel 4-Thioquinazoline Derivatives Containing Chalcone Moiety

Abstract: A series of novel 4-thioquinazoline derivatives containing chalcone moiety were designed, synthesized and systematically evaluated for their antiviral activity against TMV. The bioassay results showed that most of these compounds exhibited moderate to good anti-TMV activity. In particular, compounds M 2 and M 6 possessed appreciable protection activities against TMV in vivo, with 50% effective concentration (EC50) values of 138.1 and 154.8 μg/mL, respectively, which were superior to that of Ribavirin (436.0 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…A series of novel 4-thioquinazoline derivatives containing chalcone moiety were planned and produced (Wan et al, 2015). Compounds M2 and M6 were characterized by interesting protection properties in vivo, better than those observed with ribavirin.…”
Section: Synthetic Productsmentioning
confidence: 99%
“…A series of novel 4-thioquinazoline derivatives containing chalcone moiety were planned and produced (Wan et al, 2015). Compounds M2 and M6 were characterized by interesting protection properties in vivo, better than those observed with ribavirin.…”
Section: Synthetic Productsmentioning
confidence: 99%
“…Benzoquinazoline compounds have been reported to exhibit an interesting antiviral activity which was why evaluation of recently prepared 2-thioxo-based benzo[g] quinazolin-4(3H)-ones was reported against herpes simplex and coxsackie virus (Al-Salahi et al, 2016). Systematic evaluation of a series of thioquinazoline against Tobacco Mosaic Virus (TMV) led to the discovery of quinazolin-4-yl based prop-2-en-1-one that exhibited encouraging protection properties (EC50 = 138.1 μg/mL) upon TMV in vivo, which was over three times more active than Ribavirin (EC50 = 436.0 μg/mL) standard (Wan et al, 2015). A series of quinazoline prepared via Schiff bases formation were screened against herpes simplex virus-1 (KOS), virus-2 (G) and vaccinia virus (Ali et al, 2007), wherein (E)-3-((2-hydroxybenzylidene) amino)-2-phenyl quinazolin-4 (3H)-one emerged as the most promising antiviral motif against the entire tested virus .…”
Section: Antiviral Activitymentioning
confidence: 99%
“…As important natural products, flavonoids, and isoflavones exist in edible plants . Chalcone belongs to the core skeleton unit of isoflavones and flavonoids, having a broad‐spectrum of biological activities such as anti‐inflammatory, antibacterial, antiproliferative, insecticidal, antioxidant, antiviral, antifungal, and anticancer . Chu et al reported a series of chalcone derivatives with cationic antimicrobial peptides, and showed that the resistant bacteria MRSA, KPC, and NDM have good bactericidal activities .…”
Section: Introductionmentioning
confidence: 99%